CONSTRUCTED WETLAND AT GALUGA LANDFILL FOR LEACHATE TREATMENT: A SUSTAINABLE APPROACH - Elvira Apriana; Intan Supraba; Won Kim (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
Aim: This study aims to treat leachate by using the constructed wetland. Moreover, the study of the usage of solid waste as a part of constructed wetland was also carried out to analyze the potential of solid waste utilization as filter media. Methodology and Results: Two different alternatives were proposed to obtain the best system, i.e., conventionally constructed wetlands with gravel, sand, and rock as the filtration media, and constructed wetlands that utilize solid waste as the media. The leachate was treated in a constructed wetland using the pandan plant through a phytoremediation process. The results showed that constructed wetlands were able to reduce BOD, COD, nitrate, and phosphate concentrations up to 87.3%, 87.7%, 86%, and 99.7% in a conventionally constructed wetland, also up to 77.1%, 76.9%, 98%, and 98.9% in constructed wetland using solid waste. The analysis results show that the TSS value still exceeds the quality standard due to suspended particles in the water. Conclusion, significance, and impact study: The results showed that constructed wetland significantly affected the reduction of BOD, COD, nitrate, and phosphate but did not significantly reduce TSS. Therefore, additional technology, such as a sedimentation tank, is needed. This ecologically constructed wetland is the first step in achieving sustainable development.